Modern Architectural Design and Architect Performance in Terms of Intellectual Capital and Competence Through Leadership - Maringka, Breeze; Sebayang, Nusa (KnE Social Sciences, 2024)
This study aimed to analyze the impact of intellectual capital and competence on leadership and analyze the impact of intellectual capital and competence and leadership on the performance of architects. The sample in this study was 200 architects. The data analysis technique used structural equation modeling (SEM) analysis. The results of the analysis showed that intellectual capital and competence had an impact on leadership. Intellectual capital and competence had an impact on the performance of an architect. Leadership had an impact on the performance of an architect. Intellectual capital and competence had an impact on the performance of the Architect through leadership. Keywords: leadership, architect performance, competence, intellectual capital